2003
DOI: 10.3748/wjg.v9.i6.1370
|View full text |Cite
|
Sign up to set email alerts
|

In situexpression and significance of B7 costimulatory molecules within tissues of human gastric carcinoma

Abstract: ICOS-B7H costimulatory pathway may be predominant at the site of gastric carcinoma. B7-1mRNA might be the basis of ICOS-B7H interaction. ICOS-B7H interaction induces the production of IL-10 which inhibits the antitumor immune responses. Therefore, it is supposed that ICOS-B7H costimulatory pathway may be involved in the negative regulation of cell-mediated immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
0
25
1
Order By: Relevance
“…We also examined expression of B7h, which is a ligand for ICOS, but no obvious expression in surgically resected specimens of non-small cell lung cancer was noted (data not shown). Expression of two other B7 family members, B7.1 and B7.2, is undetectable or low in most tumor cells (23)(24)(25). Thus, expression of B7 family members differs among tumor tissues.…”
Section: Discussionmentioning
confidence: 98%
“…We also examined expression of B7h, which is a ligand for ICOS, but no obvious expression in surgically resected specimens of non-small cell lung cancer was noted (data not shown). Expression of two other B7 family members, B7.1 and B7.2, is undetectable or low in most tumor cells (23)(24)(25). Thus, expression of B7 family members differs among tumor tissues.…”
Section: Discussionmentioning
confidence: 98%
“…[32][33][34][35][36] Importantly, emerging evidence demonstrated that EBV is present in a considerable amount of tumor cells of gastric cancer patients worldwide. Studies confirmed that EBV-positive gastric cancer cell line (AGS-EBV) was resistant to the chemotherapy drugs docetaxel and 5-fluorouracil as compared with EBV-negative cells (AGS).…”
Section: E1249558-10mentioning
confidence: 99%
“…B7-H1 forms and maintains an immunosuppressive microenvironment by inhibiting the proliferation of activated T cells and inducing the apoptosis of T cells [4]. B7-H1 is over-expressed in tumor cells compared with normal gastric epithelial cells [57]. Increased B7-H1 expression has also been detected in human gastric epithelial cells in cases of Helicobacter pylori (HP) infection [8].…”
Section: Introductionmentioning
confidence: 99%